Innovative partnerships for agricultural finance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2017)
Blended finance in the agricultural sector deserves its own debate. This is why the Technical Centre for Agricultural and Rural Cooperation (CTA) together with the EC Directorate-General for International Cooperation and Development (DG DEVCO) organised the first international conference on Blending for Agriculture (“Blending4Ag”) in November 2016 in Brussels. The conference brought together an impressive group of financiers, high-level agricultural experts, policy-makers and practitioners to share lessons and best practices in designing and implementing blending. This conference focused on how public finance for smallholder agriculture can achieve the greatest possible leverage in terms of private investments in developing countries.